Radiocarbon (14C) Analysis of Carbonaceous Aerosols: Revisiting the Existing Analytical Techniques for Isolation of Black Carbon - Dasari, Sanjeev; Widory, David (Frontiers in Environmental Science, 2022)
Air pollution, a complex cocktail of different components, exerts an influence on climate/human health both locally and away from source regions. The issue of air pollution is often closely linked to carbonaceous aerosols, the assessment of climate/air quality/health impact of which remains associated with large uncertainties. Black carbon (BC) —a product of incomplete combustion— is a potent climate warming agent and one of the central components to this issue. An accurate knowledge of BC emitting sources is necessary for devising appropriate mitigation strategies and policies to reduce the associated climate/environmental burden. The radiocarbon isotope (14C or carbon-14) fingerprinting allows for an unambiguous and quantitative constraining of the BC sources and is therefore a well-popularized method. Here, we review the existing analytical techniques for the isolation of BC from a filter matrix for conducting 14C-based investigations. This work summarizes the protocols in use, provides an overarching perspective on the state-of-the-art and recommendations for certain aspects of future method development.